Neuroligin Trafficking Deficiencies Arising from Mutations in the α/β-Hydrolase Fold Protein Family - De Jaco, Antonella (American Society for Biochemistry and Molecular Biology, 2010)
Despite great functional diversity, characterization of the α/β-hydrolase fold proteins that encompass a superfamily of hydrolases, heterophilic adhesion proteins, and chaperone domains reveals a common structural motif. By incorporating the R451C mutation found in neuroligin (NLGN) and associated with autism and the thyroglobulin G2320R (G221R in NLGN) mutation responsible for congenital hypothyroidism into NLGN3, we show that mutations in the α/β-hydrolase fold domain influence folding and biosynthetic processing of neuroligin3 as determined by in vitro susceptibility to proteases, glycosylation processing, turnover, and processing rates. We also show altered interactions of the mutant proteins with chaperones in the endoplasmic reticulum and arrest of transport along the secretory pathway with diversion to the proteasome. Time-controlled expression of a fluorescently tagged neuroligin in hippocampal neurons shows that these mutations compromise neuronal trafficking of the protein, with the R451C mutation reducing and the G221R mutation virtually abolishing the export of NLGN3 from the soma to the dendritic spines. Although the R451C mutation causes a local folding defect, the G221R mutation appears responsible for more global misfolding of the protein, reflecting their sequence positions in the structure of the protein. Our results suggest that disease-related mutations in the α/β-hydrolase fold domain share common trafficking deficiencies yet lead to discrete congenital disorders of differing severity in the endocrine and nervous systems.